Ghori: an echo of deity and the Ethos of Kaliabor Region of Assam - Bordoloi, Saswati (Universitas Indraprasta PGRI, 2021)
Temples are regarded as the most sacred place among all the artefacts. The temple in India is originated as a place of cult centre or a place of worship. Temples are represented as a social organisation and a centre for economic and cultural activities. ‘Shakti-Dham’ Kamakhya temple of Assam, India has a glorious place in the religious field. Possession in Assam is a powerful kind of performance exists in many ways. ‘Ghori’ or ‘Goxani Utha’ is one kind of powerful performance has occurred in the Kamakhya temple of Silghat, Assam. This paper discusses aspects of spirit possession in relation to a particular festival celebrated annually in Kamakhya temple of Silghat, and the social ethos and folk beliefs of Kaliabor region and its impacts on society as well.